Analyzing Research Trends and Future Prospects in Islamic Capital Markets through Bibliometric Mapping - Judijanto, Loso; Efendi, Efendi; Ode, Haruni; Sipayung, Baren (The Es Accounting And Finance, 2024)
This study conducts a comprehensive bibliometric analysis of the Islamic finance field, utilizing VOSviewer to map out the scholarly landscape and investigate author collaborations, thematic clusterization, and evolving research trends. Our analysis identifies key thematic clusters centered on Islamic banking, Sharia law, and various financial instruments like Sukuk, along with the examination of market dynamics such as volatility and the impact of global disruptions like the COVID-19 pandemic. The study highlights the multidimensional nature of Islamic finance research and pinpoints areas with potential for deeper investigation, particularly in the integration of technology and ethical finance principles into Islamic financial practices. Furthermore, the exploration of author collaboration networks reveals a robust academic community with influential scholars at the core, facilitating a dynamic exchange of ideas and fostering significant research developments. The findings suggest promising directions for future research, emphasizing the need for further integration of interdisciplinary approaches and emerging technologies in the field of Islamic finance. This study serves as a valuable resource for academics, practitioners, and policymakers engaged in Islamic finance, offering insights that can drive future innovations and collaborations in the sector.